Pengaruh Kualitas Layanan Terhadap Kepuasan Konsumen pada Toko Ritel Pasar dan Ritel Toko Madura Menggunakan Pendekatan Model RSQS - Ardian Eka Wijaya; Imam Safi'i (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to compare the service quality of traditional market retail and Madurese stores and analyze the influence of Retail Service Quality Scale (RSQS) dimensions on consumer satisfaction. The method used is quantitative explanatory with a comparative-verification design. A sample of 100 respondents was selected using purposive sampling. The t-test results show that in traditional market retail only one dimension has a significant effect, namely store atmosphere (p = 0.034), while in Madurese stores there are three significant dimensions: cleanliness (p = 0.049), product arrangement (p = 0.010), and payment flexibility (p = 0.011). Multiple linear regression tests show that all RSQS dimensions simultaneously have a significant effect on consumer satisfaction, both in traditional market stores (F = 37.255; p = 0.000) and Madurese stores (F = 26.838; p = 0.000). These findings confirm that consumer preferences for service quality are influenced by cultural and operational contexts. Madurese retail has proven superior in terms of cleanliness, orderliness, and payment systems, while traditional markets rely more on shopping convenience. This study recommends improving service quality based on local wisdom to increase customer satisfaction.